Use of flow cytometry to screen chemotherapeutants with portential to control of Neoparamoeba pemaquidensis infection in Atlantic salmon, Salmo salar - Bagley, CA; Hayball, J; Lyons, B; Barbara Nowak; Crosbie, PBB (2002)
No description available